2008
DOI: 10.1002/pc.20420
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion and mechanical properties studies of UDMA based materials for producing dental posts

Abstract: Nanocomposites are a relatively new material in producing fiber re‐enforced dental posts. The mechanical properties of nanocomposites, which strongly associate with the resin matrix, nanoparticles, and the interface between inorganic fillers and organic matrix, play an important role in determining the quality of dental posts. This work was to investigate the effect of degree of conversion (DC) and silanization of fillers on the mechanical properties of nanocomposties. Experimental Urethane dimethacrylate (UDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The lower viscosities of the monomers facilitated the migration of free radicals and increased the crosslinking density . However, it has also been reported that the depth of curing appeared to be less in certain UDMA composites because of a greater mismatch in the refractive index between the monomer and filler . In addition to the resin matrix, filler particles have also been shown to possess a direct influence on the degree of curing of composite materials .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower viscosities of the monomers facilitated the migration of free radicals and increased the crosslinking density . However, it has also been reported that the depth of curing appeared to be less in certain UDMA composites because of a greater mismatch in the refractive index between the monomer and filler . In addition to the resin matrix, filler particles have also been shown to possess a direct influence on the degree of curing of composite materials .…”
Section: Discussionmentioning
confidence: 99%
“…Unreacted monomers may leach from the polymerized material and irritate the soft tissue . Furthermore, monomers trapped in the restorations may reduce the mechanical properties . Many studies have shown the correlation between the % DC and hardness, flexural strength, and modulus of elasticity of dental resin composites .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the mechanical performance, there are also increasing concerns with the quality of curing when light‐cured dental resin composites are used. Attenuation of the light with time and distance may lead to a low degree of conversion and a shallow curing depth, thereby causing unpolymerized or partially polymerized resins of the final restoration . Low conversion of monomers and/or shallow curing depths will further negatively influence the mechanical properties and dimensional stability of the restoration .…”
Section: Introductionmentioning
confidence: 99%